2020
DOI: 10.18632/aging.202305
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of circFASTKD1 ameliorates myocardial infarction by promoting angiogenesis

Abstract: Circular RNAs (circRNAs), a novel class of endogenous long non-coding RNAs, have attracted considerable attention due to their closed continuous loop structure and potential clinical value. In this study, we investigated the function of circFASTKD1 in vascular endothelial cells. CircFASTKD1 bound directly to miR-106a and relieved its inhibition of Large Tumor Suppressor Kinases 1 and 2, thereby suppressing the Yes-Associated Protein signaling pathway. Under both normal and hypoxic conditions, the ectopic expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Additionally, when ectopically or excessively expressed, circFASTKD1 can directly sponge miR-106a and then increase the expression of large tumor suppressor kinases 1 and 2 (LATS1/2), suppressing the angiogenesis of vascular endothelial cells. 127 circFASTKD1 was also demonstrated to have the highest expression in human cardiac microvascular endothelial cells (HCMEC). Furthermore, loss of circNFIX enhances cardiomyocyte proliferation and angiogenesis.…”
Section: Circrnas and Infarct Healing After MImentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, when ectopically or excessively expressed, circFASTKD1 can directly sponge miR-106a and then increase the expression of large tumor suppressor kinases 1 and 2 (LATS1/2), suppressing the angiogenesis of vascular endothelial cells. 127 circFASTKD1 was also demonstrated to have the highest expression in human cardiac microvascular endothelial cells (HCMEC). Furthermore, loss of circNFIX enhances cardiomyocyte proliferation and angiogenesis.…”
Section: Circrnas and Infarct Healing After MImentioning
confidence: 99%
“…In contrast to the above circRNAs, circFASTKD1 was suggested to exert a suppressive influence on angiogenesis during MI and had the potential to be a novel prognostic biomarker in MI patients. 127 In addition, Cheng et al. 97 observed that the expression of circPostn is markedly upregulated in plasma samples of MI patients, the MI mouse model, and the I/R-treated cell model, and they speculated that circPostn expression is closely associated with MI.…”
Section: Circrnas As Diagnostic and Prognostic Biomarkers For MImentioning
confidence: 99%
“…Cardiomyocyte proliferation and angiogenesis are essential for structural and functional repair during cardiac regeneration. Gao et al demonstrated that circFASTKD1 binds directly to miR-106a and relieve its inhibition of LATS1 and LATS2, thereby suppressing the YAP signaling pathway ( 42 ). The downregulation of circFASTKD1 ameliorates MI by promoting angiogenesis through the miR-106a-LATS1/2-YAP axis ( 42 ).…”
Section: Circrna As Cerna In Cvdsmentioning
confidence: 99%
“…Gao et al demonstrated that circFASTKD1 binds directly to miR-106a and relieve its inhibition of LATS1 and LATS2, thereby suppressing the YAP signaling pathway ( 42 ). The downregulation of circFASTKD1 ameliorates MI by promoting angiogenesis through the miR-106a-LATS1/2-YAP axis ( 42 ). Another study showed that circHipk3 acts as a sponge for miR-133a to promote CTGF expression ( 43 ).…”
Section: Circrna As Cerna In Cvdsmentioning
confidence: 99%
“…Additionally, circCDYL can promote the proliferation of cardiomyocytes through the miR-4793-5p/APP pathway (14). The downregulation of circFASTKD1 induces angiogenesis and improves cardiac function and repair after myocardial infarction (123). Hsa_circ_0007623 can bind to miR-297 and acts as a sponge of microRNA-297 which promotes cardiac repair after acute myocardial ischemia and protects cardiac function (124).…”
Section: Circrna and Cvdsmentioning
confidence: 99%